Corporate tax planning and firms' information environment - Benjamin Osswald (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
This study examines whether internal information quality (IIQ) is associated with firms' external information quality (EIQ) and whether tax planning moderates this association. Based on the argument that higher internal information quality allows managers to convey higher quality information to market participants, I hypothesize and find a positive association between IIQ and EIQ. I then examine if tax planning, which prior literature shows affects external information quality due to proprietary costs of disclosure, attenuates this association. I find that the association between IIQ and EIQ is fully attenuated for firms with a high level of tax planning. A structural equation model that allows different elements of IIQ to covary and robustness tests corroborate my findings. Overall, my results imply that increased IIQ spills over to EIQ because managers convey higher quality internal information to market participants. However, proprietary costs resulting from a high level of tax planning appear to moderate this effect.
Keywords: G30; H26; M41; 330; external information quality; information asymmetry; information environment; internal information quality; tax avoidance; tax planning